Determinants of factor that affect inflation in Malaysia / Muhammad Aziz Farhan Noor Akbar - Noor Akbar, Muhammad Aziz Farhan (2022)
Inflation can occur when raw material and labor costs rise. Increasing product and service demand can produce inflation when customers pay more. This research examines the macroeconomic and microeconomic elements affecting Malaysia's inflation rate. Hence, the goal of this research is to look into the relationship and impacts of the five independent variables, which are the exchange rate (EXC), money supply (MS), unemployment rate (UR), Interest rate (IR), and the consumer price index (CPI) on the Inflation rate in Malaysia (INF). This research presents a study of Malaysia's inflation rate from the year 2015 to the year 2020. The whole year that has been observed for this research is five years. Moreover, this research uses secondary sources, and the data and information have been obtained via databases, other publications, and articles. All the information we gathered came from Google Scholar, Trading Economic, Investing.com, and IndexMundi. In addition, the study employs descriptive analysis, correlation analysis, regression analysis, F- test, Ttest, multicollinearity test, and coefficient of determination (R2) to determine whether the independent variables are significant or insignificant to the Malaysia inflation rate. Furthermore, it determines whether the independent variables have a negative or positive relationship to Malaysia's inflation rate. The overall findings of this research shows that all independents variable impact the dependent variables.